Surveillance of HIV, hepatitis B virus, and hepatitis C virus in an estonian injection drug-using population: sensitivity and specificity of testing syringes for public health surveillance. - Uuskula, Anneli; Heimer, Robert; Dehovitz, Jack; Fischer, Krista; McNutt, Louise-Anne (The Journal of infectious diseases, 2006)
Surveillance of bloodborne infections among injection drug users (IDUs) can be accomplished by determining the presence of pathogen markers in used syringes. Parallel testing of returned syringes and venous blood from IDUs was conducted to detect antibodies to human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV). Syringe surveillance for HIV yielded a sensitivity and specificity of 92% and 89%, respectively, and provided a reasonable estimate of the prevalence of HIV among participants. Because sensitivity for HBV (34%) and HCV (55%) was low, syringe testing may be useful for surveillance of hepatitis over time but not for estimation of prevalence.
Keywords: Adolescent; Adult; Estonia; Female; Hepacivirus; Hepatitis B; Hepatitis B virus; Hepatitis C; HIV Infections; HIV-1; Humans; Male; Middle Aged; Population Surveillance; Predictive Value of Tests; Prevalence; Sensitivity and Specificity; Substance Abuse, Intravenous; Syringes